2021
DOI: 10.3390/nano11020516
|View full text |Cite
|
Sign up to set email alerts
|

ECM-Mimetic Nylon Nanofiber Scaffolds for Neurite Growth Guidance

Abstract: Numerous nanostructured synthetic scaffolds mimicking the architecture of the natural extracellular matrix (ECM) have been described, but the polymeric nanofibers comprising the scaffold were substantially thicker than the natural collagen nanofibers of neural ECM. Here, we report neuron growth on electrospun scaffolds of nylon-4,6 fibers with an average diameter of 60 nm, which closely matches the diameter of collagen nanofibers of neural ECM, and compare their properties with the scaffolds of thicker 300 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 62 publications
(47 reference statements)
1
22
0
Order By: Relevance
“…As we reported previously [42], nylon fibers can significantly increase the proliferation rate of neuroblastoma cells. Since even minor changes in the nanotopology of a material can cause significant changes in cell behavior [4], we tested the cytotoxicity of the nanoparticle decorated materials.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…As we reported previously [42], nylon fibers can significantly increase the proliferation rate of neuroblastoma cells. Since even minor changes in the nanotopology of a material can cause significant changes in cell behavior [4], we tested the cytotoxicity of the nanoparticle decorated materials.…”
Section: Discussionsupporting
confidence: 80%
“…Several studies reported preparation and successful application of artificial nerve conduits based on electrospun fibrous materials in biological test systems [13,62,63]. However, relatively few works are deploying fiber nanomaterials with fiber diameters of 100 nm due to technical difficulties of manufacturing [42]. The use of composite light-converting nanomaterials demonstrates efficiency in stimulating differentiation of neural cells [59,60]; therefore, we believe that the combination of topology-mediated stimulation with thermally induced control of cellular activity is of practical interest for the creation of neurosurgical implants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These anisotropic meshes provide the neural population with a path of least resistance for growth in a general direction. 187,197 This concept is useful for matrix-assisted neurite guidance which makes it possible to model nerve fibers in vitro. 198 Besides being recruited as aligned 3D scaffolds or 2D substrates, they can be used as sacrificial fibers to imprint another substrate with the anisotropic fiber pattern to guide axonal growth.…”
Section: Fibrous Scaffoldsmentioning
confidence: 99%